Optogenetic Control of RhoA to Probe Subcellular Mechanochemical Circuitry. Issue 1 (7th February 2020) - Cavanaugh, Kate E.; Oakes, Patrick W.; Gardel, Margaret L.
Abstract: Spatiotemporal localization of protein function is essential for physiological processes from subcellular to tissue scales. Genetic and pharmacological approaches have played instrumental roles in isolating molecular components necessary for subcellular machinery. However, these approaches have limited capabilities to reveal the nature of the spatiotemporal regulation of subcellular machineries like those of cytoskeletal organelles. With the recent advancement of optogenetic probes, the field now has a powerful tool to localize cytoskeletal stimuli in both space and time. Here, we detail the use of tunable light‐controlled interacting protein tags (TULIPs) to manipulate RhoA signaling in vivo. This is an optogenetic dimerization system that rapidly, reversibly, and efficiently directs a cytoplasmic RhoGEF to the plasma membrane for activation of RhoA using light. We first compare this probe to other available optogenetic systems and outline the engineering logic for the chosen recruitable RhoGEFs. We also describe how to generate the cell line, spatially control illumination, confirm optogenetic control of RhoA, and mechanically induce cell‐cell junction deformation in cultured tissues. Together, these protocols detail how to probe the mechanochemical circuitry downstream of RhoA signaling. © 2020 by John Wiley & Sons, Inc. Basic Protocol 1 : Generation of a stable cell line expressing TULIP constructs Basic Protocol 2 : Preparation of collagen substrate for imaging Basic Protocol 3 : Transient transfection for visualization of downstream effectors Basic Protocol 4 : Calibration of spatial illumination Basic Protocol 5 : Optogenetic activation of a region of interest